REFLECTIONS ON THE USE OF SMARTPHONES FOR EDUCATIONAL PURPOSES IN SCHOOLS - Silva Daltio, Eva; França dos Santos, George; Nadler Prata, David (LINKSCIENCEPLACE, 2026)
This article has the purpose to reflect the use of smartphones in schools in order to identify the challenges and pertinent issues within the social dynamics and the contemporary school. In this perspective, relevant conceptions for the use of this technology are discussed, considering contributions of digital technologies of information and communication for the construction of new ways to teach and to learn. For the development of these reflections, the challenge issues for the school of today were debated. Facing a society distinguished by mobility facilities as the smartphone; the concept of "mobility, pervasiveness and ubiquity" are explored here as characteristics of a society driven by digital technologies and in whose contextual situation the school is immersed. They are also presented as consequent changes in people’s lives through the title "social relations and smartphone": relationships that are modifiable an exponential intensity through social networks and the diversity of applications that favor formation of virtual groups from interests Common In the section "the popularization of today’s smartphones and school", some official indicators of smartphone usage are indicated, suggesting an eminence of a methodological action for its use in the practice of the classroom. This action allows the student to act as the protagonist of learning, while contributing to a more solid and higher quality teaching. Statistical data refer to conclusions of statements contained within the scope of this approach.